The Role of Photobiomodulation in Cell Repair - Yvona Zivic (Dermatology, 2024)
Photobiomodulation is a non-invasive treatment modality acting at different biological levels through the non-thermal transfer of photons to the living matter via a photoelectric effect, inducing photochemical reactions in treated cells. The objective of this article is to review the literature on Photobiomodulation, its different fields of application and mechanisms of action, for establishing a comprehensive summary of evidence. The search strategy initially run searches in scientific databases MEDLINE, PubMed, EMBASE and Cochrane registries from 1990 up to March 2020, with entries Photobiomodulation, LLLT-LEDT, PDT, Photobiology, Cytochrome c Oxidase. Selection criteria was based on preferably inclusion of randomized clinical trials (RCTs), systematic reviews (SR) and studies providing qualitative and quantitative data with the best consistency, in a field where hetero geneity of light parameters is often a difficulty to comparison of findings. Publised expert opinions were also considered. A total of 80 publications were reviewed out of a thousand obtained from databases, among which were retained 9 RCTs, 6 systematic reviews, 3 meta-analysis and 2 case-reports. Differences were found in treatment parameters as wavelength, dosage, energy output, treatment length, performances of light-sources, quantity of diodes and single power of these, which may explain the paucity of high-level body of evidence in Cochrane databases. However, numerous state-of-the- art researches are also found, led by dedicated research teams paving the way to standardized methods of evaluation and comprehension of light-biological-tissues interaction and optimization of outcomes in a promising field.